Lung cancer CT screening: psychological responses in the presence and absence of pulmonary nodules - Clark, Marcia E.; Bedford, Laura E.; Young, Ben; Robertson, John F.R.; das Nair, Roshan; Vedhara, Kavita; Littleford, Roberta; Sullivan, Francis M.; Mair, Frances S.; Schembri, Stuart; Rauchhaus, Petra; Kendrick, Denise (Elsevier, 2018)
Objectives: To determine the psychological response (thoughts, perceptions and affect) to a diagnosis of pulmonary nodules following a novel antibody blood test and computed tomography (CT) scans within a UK population.